Identification of the early cretaceous granitic pluton and tectonic implications in the middle gangdese belt, southern tibet - Wang, Qingling; Meng, Yuanku; Wei, Youqing; Jiang, Li; Wang, Zhenzhen; Mao, Guangzhou (Frontiers in Earth Science, 2022)
The Early Cretaceous magmatic exposures are sporadic in the Gangdese magmatic belt, thus the finding of the new exposure is key to understanding the evolution scenarios of the Neo-Tethys Ocean and geological background of southern Tibet during the Early Cretaceous. In this contribution, we undertook systematic geochronology, whole-rockgeochemistry and zircon Lu-Hfisotope studies on a newly identified granitic pluton in the middle Gangdese belt (Quesang area), southern Tibet. The results show that zircon U-Pb dating of three representative samples yielded a weighted age of 119.9±1.4Ma, 117.3±2.7Ma and 114±1.3Ma, respectively, which indicate the emplacement and crystallization age belong to Aptian stage of the Early Cretaceous in response to the northward subduction of the Neo-Tethys oceanic lithosphere beneath the Lhasa terrane. The in situ zircon Lu-Hf isotopic analyses indicate that ƐHf(t) values of the granitic pluton are predominantly positive ranging from 7.2 to 11.4, and minor zircons show negative ƐHf(t) values (-6.26), implying that a small amount of ancient continental crustal material might have participated in the magma evolution. Geochemically, the samples are enriched in large ion lithophile elements (LILE) and light rare earth elements (LREE), but depleted in heavy rare earth elements (HREE), indicating arc-type geochemical characteristics or subduction-related tectonic setting. In addition, combined with mineral assemblages, zircon Lu-Hf isotopic features and low A/CNK ratios of 0.91 to 1.10, the samples have a close affinity with I-type granitoid rocks. Zircon oxygen fugacity results show that Ce4+/Ce3+ values of 185 to 12, with a mean value of 78, indicating a low oxygen fugacity setting similar to Chile ore-barren granitic plutons. In combination with published data, we argue that the Gangdese magmatic belt may have developed continuous magmatism (145-105 Ma), and the notion of magmatic lull might deserve more consideration during the Early Cretaceous. The Early Cretaceous granite pluton might be the result of the northward subduction of Neo-Tethys oceanic lithosphere beneath the Lhasa terrane at a normal angle.